Statistics - Ilersic, A. R. (London HFL Publishers, 1964)
The chapters of Economics and social statistics have been brought up to date and extended with the addition of a few new sections, as has been the chapter on vital statistics
osc 24/10/2019
Loans
Keywords: Statistics; Social statistics